3D printing of tantalum parts based on low molecular mass organic gel system. (November 2019) - Qin, Qian; Yang, Fang; Zhang, Xinyue; Shi, Tao; Shao, Yanru; Sun, Haixia; Chen, Cunguang; Hao, Junjie; Guo, Zhimeng
Abstract: In this study, 3D gel printing based on a low molecular mass organic gel system was employed to fabricate complex-shaped Ta parts. As opposed to a polymeric gel system, this system was initiated by heat transition. To obtain suitable printing slurry with 62 vol% solid content, 2.5 wt% resin was introduced to improve green body strength and 0.55 wt% oleic acid was added to modify the viscosity. As a result, the printed samples had relatively good surface quality without defects or pores observed on the surface. Ta particles were closely bound by dibenzylidene sorbitol (DBS) gelators. After sintering, a uniform shrinkage was obtained with a shrinkage of 11%, but the surface quality of the as sintered samples was improved. Sintering decreased the surface roughness from 4.0 μm to 2.8 μm. Besides, the as-sintered Ta samples had a relatively dense and homogenous microstructure. The relative density of the as-sintered sample was about 98%. Therefore, 3D gel printing is a promising method to prepare complex-shaped Ta parts with minimal material waste. Graphical abstract: Unlabelled Image Highlights: Ta parts with a relative density of about 98% was prepared by 3D gel printing. Low molecular mass organic gel system was introduced in to 3D gel printing. The printed Ta parts had good surface quality and high dimensional accuracy. One promising method was proposed to prepare complex-shaped Ta parts.